Fababrication of higt -aspect-ration micro stucres using uv-liga technology - Hang, Nguyen Thi Minh; Hung Ho, Chien-; Hung, vU Ngoc; Thuy, Nguyen Phu (VNU Journal of Science: Mathematics - Physics, 2005)
Abstract